2018
DOI: 10.1186/s13071-018-2827-3
|View full text |Cite
|
Sign up to set email alerts
|

A combined effort to avoid strongyle infection in horses in an oceanic climate region: rotational grazing and parasiticidal fungi

Abstract: BackgroundAn approach to preventing strongyle infection in horses was tested, comprising rotational pasturing and the administration of spores of two parasiticidal fungi, Mucor circinelloides and Duddingtonia flagrans.MethodsTwenty-two adult Spanish Sport Horses were dewormed with ivermectin (1 mg pour-on/kg body weight) and then randomly divided into three groups. G-1 was maintained with continuous grazing, and G-2 and G-3 were kept on a four-paddock rotation system. Commercial pelleted feed (2.5 kg/horse) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…However, excluding the study of Healey et al, the effect has been demonstrated by same active researchers by same methods in same climate conditions. Climate in Brazil, in which most of these studies have been carried out and in subtropical environment of southern Louisiana (Baudena et al, 2000), and in Spain (Paz-Silva et al, 2011;Herná ndez et al, 2016Herná ndez et al, , 2018 cannot tell the utilization potential of fungal cultures in climates outside these countries. Ferná ndez et al (1997) have reported that dry climate conditions affected the transmission of infective larvae resulting in low numbers of larvae on the herbage, and during the rainy periods a significant reduction in the number of larvae recovered around fungal containing pats.…”
Section: Generalizability Of the Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, excluding the study of Healey et al, the effect has been demonstrated by same active researchers by same methods in same climate conditions. Climate in Brazil, in which most of these studies have been carried out and in subtropical environment of southern Louisiana (Baudena et al, 2000), and in Spain (Paz-Silva et al, 2011;Herná ndez et al, 2016Herná ndez et al, , 2018 cannot tell the utilization potential of fungal cultures in climates outside these countries. Ferná ndez et al (1997) have reported that dry climate conditions affected the transmission of infective larvae resulting in low numbers of larvae on the herbage, and during the rainy periods a significant reduction in the number of larvae recovered around fungal containing pats.…”
Section: Generalizability Of the Resultsmentioning
confidence: 99%
“…Daily treatments are previously and more recently recommended (Fernandez et al, 1997(Fernandez et al, , 1999Healey et al, 2018), but the dose administered to the animals may be adjusted according to the isolate employed (Buzatti et al, 2015). On the other hand, a single dose (Tavela et al, 2013), twice a week administration (Herná ndez et al, 2018) and longer intervals (Buzatti et al, 2015) can also be effective alternatives to the daily treatment.…”
Section: Usefulness the Results: Practical Perspectivementioning
confidence: 99%
See 3 more Smart Citations